Predictors and outcomes of disseminated tuberculosis in an intermediate burden setting - Meira, L. (2019)
Setting: University-affiliated hospital located in Porto, North Portugal, an area with a low to intermediate incidence of tuberculosis (TB). Objective: To identify predictors and outcomes of disseminated TB (dTB). Design: A cohort of patients diagnosed with TB between 2007 and 2013 was retrospectively analysed. Patients with dTB criteria were characterized and compared to single organ TB cases. Factors independently associated with dTB were determined by multivariate logistic regression analysis. Results: A total of 744 patients were analysed, including 145 with dTB. Independent risk factors for dTB were pharmacological immunosuppression (OR 5.6, 95% CI 2.8–11.3), HIV infection (OR 5.1, 95% CI 3.1–8.3), chronic liver failure or cirrhosis (OR 2.3, 95% CI 1.4–4.1) and duration of symptoms (OR 2.3, 95% CI 1.4–3.8). Compared to single organ TB, the clinical presentation of dTB patients differed by the absence of haemoptysis (OR 3.2, 95% CI 1.3–8.4) and of dyspnoea (OR 1.9, 95% CI 1.2–3.1), presence of weight loss (OR 1.8, 95% CI 1.1–2.9), night sweats (OR 1.7, 95% CI 1.1–2.7) and bilateral lung involvement (OR 4.4, 95% CI 2.8–7.1). Mortality and time until culture conversion were higher for dTB patients, although not reaching statistical significance. Conclusion: Immunosuppressive conditions and chronic liver failure or cirrhosis were associated with increased risk of dTB. The haematogenous spread may be dependent on longer symptomatic disease and usually progresses with bilateral lung involvement.